2016
DOI: 10.1186/s11689-016-9135-z
|View full text |Cite
|
Sign up to set email alerts
|

Atypical functional connectivity in resting-state networks of individuals with 22q11.2 deletion syndrome: associations with neurocognitive and psychiatric functioning

Abstract: Background22q11.2 deletion syndrome (22q11DS) is a neurogenetic condition associated with deficits in neuropsychological functioning and psychiatric disorders. This deletion confers a high risk for the development of psychosis, as approximately 30–45 % of individuals develop psychosis in adulthood. Previous reports of resting-state functional magnetic resonance imaging (rs-fMRI) functional connectivity patterns in 22q11DS have demonstrated that atypical connectivity is associated with both the emergence and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 74 publications
(85 reference statements)
3
29
0
Order By: Relevance
“…We observed no difference in functional connectivity within the CEN and the SN. This result is in contrast with recent findings in 22q11DS [Mattiaccio et al, 2016], but is in line with previous results from our group . This discrepancy in the results may be due to the use of different acquisition, processing and analysis techniques as well as to different sample characteristics.…”
Section: Impaired Within-and Between-network Connectivity In Patientssupporting
confidence: 85%
See 3 more Smart Citations
“…We observed no difference in functional connectivity within the CEN and the SN. This result is in contrast with recent findings in 22q11DS [Mattiaccio et al, 2016], but is in line with previous results from our group . This discrepancy in the results may be due to the use of different acquisition, processing and analysis techniques as well as to different sample characteristics.…”
Section: Impaired Within-and Between-network Connectivity In Patientssupporting
confidence: 85%
“…However, few studies showed white matter impairments [Radoeva et al, ] or aberrant functional activation [Gothelf et al, ; Montojo et al, ] associated with executive dysfunctions in patients with the syndrome. On the opposite, in a recent study investigating functional connectivity within resting‐state networks [Mattiaccio et al, ], the authors found no association between altered connectivity and executive functions measures. A number of studies (reviewed in [Scariati et al, ]) further reported an association between impairments in long‐range connections and psychotic symptoms in 22q11DS.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite these promises of dynamic fMRI analysis, functional neuroimaging research in 22q11DS has so far mostly focused on static functional features (17,80,54,84,55), often targeting only specific functional networks such as the DMN (66,85). The studies who explicitly investigated psychotic symptoms in 22q11DS showed correlations of DMN dysconnectivity with prodromal psychotic symptoms (17), as well as successful discrimination between patients at high vs. low risk based whole-brain rs-fMRI (80) and hypoconnectivity of DMN, SN, anterior cingulate cortex (ACC) and frontoparietal network (FPN; 84).…”
Section: Introductionmentioning
confidence: 99%